2021
DOI: 10.1007/s00261-021-03003-0
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal venous sampling in primary hyperaldosteronism: correlation of hormone indices and collimated C-arm CT findings

Abstract: Purpose To evaluate the feasibility and effect of an approach to adrenal venous sampling (AVS) analysis by combining established selective cortisol and aldosterone indices with the acquisition of a collimated C-arm CT(CACTColl). Methods Overall, 107 consecutive patients (45f,62 m; 54 ± 10 years) undergoing 111 AVS procedures without hormonal stimulation from 7/13 to 2/20 in a single institution were retrospectively analysed. Hormone levels were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(103 reference statements)
0
2
1
Order By: Relevance
“…The value of CBCT during AVS has long been investigated, and most studies have suggested that CBCT is a useful tool for identifying RAV, thereby improving the success rate of AVS [11][12][13][14][15][16][17]. However, the present study showed contrasting results, in which a similar success rate was noted in patients with or without the assistance of CBCT (88.4% vs. 82.3%, P = 0.347).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The value of CBCT during AVS has long been investigated, and most studies have suggested that CBCT is a useful tool for identifying RAV, thereby improving the success rate of AVS [11][12][13][14][15][16][17]. However, the present study showed contrasting results, in which a similar success rate was noted in patients with or without the assistance of CBCT (88.4% vs. 82.3%, P = 0.347).…”
Section: Discussioncontrasting
confidence: 55%
“…The main difficulty associated with AVS is the cannulation of the right adrenal vein (RAV), as it is often short and exhibits several anatomical variations [8][9][10]. In previous studies, cone-beam computed tomography (CBCT) was used, which may improve the overall success rate of AVS [11][12][13][14][15][16][17]. However, CBCT is a time-consuming procedure that requires additional radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In our institution, cortisol levels from the IVC have been utilised routinely for the SI calculation. Published studies using iliac venous samples, as a surrogate for a peripheral one, are limited [ 27 , 28 ]. Whilst the small difference in cortisol levels between the IVC and REIV samples had no impact on the outcomes, the use of a more peripheral sample (e.g.…”
Section: Discussionmentioning
confidence: 99%